Homozygous familial hypercholesterolemia: Summarized case reports. (February 2017) - Widhalm, Kurt; Benke, Ina Michel; Fritz, Michael; Geiger, Harald; Helk, Oliver; Fritsch, Maria; Hoermann, Gregor; Kostner, Gerhard
Abstract: Background and aims: Homozygous familial hypercholesterolemia (hoFH) is a rare genetic disorder with potential severe atherosclerosis in the pediatric age. Methods: We report on 9 patients with hoFH, who had been diagnosed within the last 30 years and who were consequently treated with apheresis and drugs. Results: Two deaths occurred: one at age 36 years and the other at age four and a half years before effective treatment was commenced. All other patients are still in good clinical condition today, although four of them have proven aortic stenosis or arterial plaques. Conclusions: Our case report highlights that adequate treatment should start as early as possible to delay the onset of clinical manifestations of atherosclerosis. It can be assumed that the introduction of new drugs can improve the outcome and possibly lengthen the life expectancy of patients affected by hoFH. Highlights: Familial hypercholesterolemia should be diagnosed as early as possible. Apheresis treatment in subjects with homozygous familial hypercholesterolemia (hoFH) should be initiated in childhood. If hoFH is diagnosed in a patient it is important to screen his/her family.